Expert consensus statement on venovenous extracorporeal membrane oxygenation ECMO for COVID-19 severe ARDS: an international Delphi study - Ahmed A. Rabie; Alyaa Elhazmi; Mohamed H. Azzam; Akram Abdelbary; Ahmed Labib; Alain Combes; Bishoy Zakhary; Graeme MacLaren; Ryan P. Barbaro; Giles J. Peek; Marta Velia Antonini; Kiran Shekar; et al. (Annals of Intensive Care, 2023)
Abstract Background The high-quality evidence on managing COVID-19 patients requiring extracorporeal membrane oxygenation (ECMO) support is insufficient. Furthermore, there is little consensus on allocating ECMO resources when scarce. The paucity of evidence and the need for guidance on controversial topics required an international expert consensus statement to understand the role of ECMO in COVID-19 better. Twenty-two international ECMO experts worldwide work together to interpret the most recent findings of the evolving published research, statement formulation, and voting to achieve consensus. Objectives To guide the next generation of ECMO practitioners during future pandemics on tackling controversial topics pertaining to using ECMO for patients with COVID-19-related severe ARDS. Methods The scientific committee was assembled of five chairpersons with more than 5 years of ECMO experience and a critical care background. Their roles were modifying and restructuring the panel’s questions and, assisting with statement formulation in addition to expert composition and literature review. Experts are identified based on their clinical experience with ECMO (minimum of 5 years) and previous academic activity on a global scale, with a focus on diversity in gender, geography, area of expertise, and level of seniority. We used the modified Delphi technique rounds and the nominal group technique (NGT) through three face-to-face meetings and the voting on the statement was conducted anonymously. The entire process was planned to be carried out in five phases: identifying the gap of knowledge, validation, statement formulation, voting, and drafting, respectively. Results In phase I, the scientific committee obtained 52 questions on controversial topics in ECMO for COVID-19, further reviewed for duplication and redundancy in phase II, resulting in nine domains with 32 questions with a validation rate exceeding 75% (Fig. 1). In phase III, 25 questions were used to formulate 14 statements, and six questions achieved no consensus on the statements. In phase IV, two voting rounds resulted in 14 statements that reached a consensus are included in four domains which are: patient selection, ECMO clinical management, operational and logistics management, and ethics. Conclusion Three years after the onset of COVID-19, our understanding of the role of ECMO has evolved. However, it is incomplete. Tota14 statements achieved consensus; included in four domains discussing patient selection, clinical ECMO management, operational and logistic ECMO management and ethics to guide next-generation ECMO providers during future pandemic situations.